Correlation of ultrasound with histopathology for retained products of conception in medically managed abortions - Chopra, Namita; Kaur, Manpreet; Mohi, Manjit Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Medical abortion uses an anti-progestin, mifepristone (RU486), followed by a prostaglandin (misoprostol). Objective of present study was to correlate findings of transvaginal ultrasound with histopathology for retained products of conception in medical abortions. Methods: An observational, prospective study was conducted on hundred women with gestation upto 12 weeks who underwent medical abortion with excessive or prolonged post abortal vaginal bleeding. Transvaginal scan followed by uterine evacuation was done under anesthesia, followed by histopathology. Results: Analysis was done statistically using Pearson Chi- square method. Sixty five percent subjects took MTP pill by unsupervised, self-intake and 35% on prescription. Among women who took misoprostol in dose of 400mcg, 89% had RPOC on histopathology. At the dose of 800 mcg, 73.3% had retained Products of Conception (RPOC) on histopathology. The correlation was found to be statistically non-significant (p value at 5% was 1.13). Ultrasound showed echogenic mass in the uterine cavity in 62 (62%) women, increased endometrial thickness ≥10mm in 13 (13%), gestational sac with no fetal pole in 6 (6%), blood clots in uterine cavity in 6 (6%), and empty uterine cavity in 3 (3%). Seventy five percent of women had histologically proven RPOC at endometrial cut off of equal to or greater than 10mm. The sensitivity, specificity, positive and negative predictive value of transvaginal ultrasonography in detection of retained products of conception were 92%, 60%, 87.3%, 71.4% respectively. The diagnostic accuracy was 84%. Conclusions: Transvaginal ultrasound for detecting retained products of conception in medically managed abortions has a high sensitivity and positive predictive value and is useful for screening women with clinically suspected incomplete abortion who require further intervention -medical or surgical.